Vacuum fermentation integrated with separation process for ethanol production - Nguyen, Viet D. (Animo Repository, 2011)
In this study, continuous fermentation integrated with separation process at atmospheric and vacuum pressures are investigated. An initial glucose concentration of 200gL-1 was used to produce yeast cells under batch operating mode. After a period of 18-20h, a medium of 350gL-1 glucose concentration was fed continuously to the fermentation-separation column. During the continuous experiments, fermented broth was recirculated back to the fermentation-separation column. At atmospheric pressure, the dry mass concentration decreased rapidly and remained at 2.4gL-1 after long period, while glucose concentration still remained at 240gL-1. On the other hand, at vacuum pressure, a quasi-steady state condition was reached after 96h, corresponding to 4.2gL-1 of cell dry mass, 165gL-1 of glucose and 44.2gL-1 of ethanol levels in the fermentation broth and 33.2wt% of ethanol concentration at the outlet. These results indicate reduced product and substrate inhibition, suggesting that the integrated process could be used to replace the first bioreactor in a fermentation cascade system. A mathematical model was then developed and used to predict the kinetic parameters. The simulation results agreed well with experimental data. © 2011 Elsevier B.V.